Heparin binding protein is increased in chronic leg ulcer fluid and released from granulocytes by secreted products of Pseudomonas aeruginosa - Lundqvist, Katarina; Herwald, Heiko; Sonesson, Andreas; Schmidtchen, Artur (Thrombosis and Haemostasis, 2004)
Recently it was demonstrated by Gautam, et al. that release of neutrophil-borne heparin-binding protein (HBP), also known as CAP37/azurocidin, induced endothelial hyperpermeability and neutrophil efflux. Here, we show that chronic leg ulcer fluid, in contrast to wound fluid from acute wounds, contains highly increased levels of HBP. Immunohistochemistry demonstrated the presence of HBP in chronic ulcer tissues. Furthermore, secreted products of Pseudomonas aeruginosa were found to induce release of HBP from human neutrophils. Our data suggest a possible link between bacterial presence and HBPrelease in chronic ulcers.Thus, targeting HBP offers an interesting option for reduction of endothelial barrier dysfunction in chronic ulcers.
Keywords: Wound healing; inflammation; skin; blood; aprotinin